2004
DOI: 10.1007/s00213-004-1997-1
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic assessment of galanin overexpressing and galanin receptor R1 knockout mice in the tail suspension test for depression-related behavior

Abstract: Neither pharmacological nor molecular genetic manipulations of galanin altered depression-related profiles in the TST. Possible functional alterations in hippocampal 5-HT neurotransmission may have contributed to these negative results. These preliminary findings provide evidence against the hypothesis that galanin plays a central role in mouse depression-related behaviors. It remains possible that galanin modulates depression-related responses in other experimental paradigms and species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 44 publications
0
26
0
Order By: Relevance
“…However, studies on mice with genetically deleted Galr1 (Galr1-KO) showed no effect in the tail suspension test, pharmacological manipulations did not alter the depression profile (65), and such mice showed increased anxiety-like behavior in the elevated plus-maze (66). It should be noted that the 5-HT neurons in the mouse DR, in contrast to the rat DR, do not express galanin (67)(68)(69)(70) and that the KO mice, of course, lack this receptor throughout life and in all parts of the brain (body).…”
Section: Discussionmentioning
confidence: 99%
“…However, studies on mice with genetically deleted Galr1 (Galr1-KO) showed no effect in the tail suspension test, pharmacological manipulations did not alter the depression profile (65), and such mice showed increased anxiety-like behavior in the elevated plus-maze (66). It should be noted that the 5-HT neurons in the mouse DR, in contrast to the rat DR, do not express galanin (67)(68)(69)(70) and that the KO mice, of course, lack this receptor throughout life and in all parts of the brain (body).…”
Section: Discussionmentioning
confidence: 99%
“…In total, 83 unique genes were upregulated and 17 genes were downregulated by chronic fluoxetine treatment (Table 2, Supplementary Table S1). Most highly upregulated were Preproenkephalin 1, a possible quantitative trait gene for bipolar disorder (Ogden et al, 2004), and Galanin, antagonists of which prevent the behavioral effect of fluoxetine in the TST and the FST (Holmes et al, 2005;Swanson et al, 2005).…”
Section: Effect Of Chronic Fluoxetine Treatment On Hippocampal Gene Ementioning
confidence: 99%
“…[117,118] This is also supported by the phenotypic analysis of anxietyand depression-related behaviours in genetically GALR-modified mice strains. [119][120][121][122][123] Taken together, these preclinical data suggest that GALRs could serve as targets of antidepressant therapy, using either GALR1/GALR3 antagonists or GALR2 agonists. GALR3 antagonists (figure 5) are being tested in clinical trials for the treatment of depression and patents have already been issued on their use for MDD treatment.…”
Section: Galanin Receptorsmentioning
confidence: 87%